Prospective associations between psychosomatic complaints in adolescence and depression and anxiety symptoms in young adulthood: A Swedish national cohort study - Karina Grigorian; Viveca Östberg; Jonas Raninen; Johan Åhlén; Sara Brolin Låftman (Elsevier, 2023)
Background: Psychosomatic complaints are reported by high shares of adolescents in Sweden and elsewhere. Yet, little is known about to the extent to which the frequency, number, and persistence of such complaints in adolescence are associated with subsequent mental health problems. The aim of this study was to examine how the frequency, number, and persistence of psychosomatic complaints in middle and late adolescence are associated with depression and anxiety symptoms in young adulthood. Methods: A Swedish national cohort study of adolescents who were surveyed in 2017 (t1; age 15-16), in 2019 (t2; age 17-18) and in 2022 (t3; age 20-21 years) was used. Psychosomatic complaints were measured by questions on stomach ache, headache and difficulties falling asleep at t1 and t2. Depression and anxiety symptoms were measured by the Patient Health Questionnaire-4 (PHQ-4) at t3. Multivariable binary logistic regression analyses stratified by gender were based on data from t1, t2 and t3 (n = 2779). Results: The frequency, number, and persistence of psychosomatic complaints during adolescence were associated with symptoms of depression and anxiety in young adulthood. Both earlier (at t1 only) and more recent (at t2 only) complaints were linked to subsequent depression and anxiety symptoms, while persistent (at both t1 and t2) psychosomatic complaints showed stronger associations in girls. Conclusions: Psychosomatic complaints in adolescence were associated with depression and anxiety symptoms in young adulthood. This was true for the frequency, number, and persistence of psychosomatic complaints. Among girls, those who reported persistent psychosomatic complaints from middle to late adolescence had the highest likelihood of reporting subsequent depression and anxiety symptoms. Taken together, the results indicate that psychosomatic complaints during adolescence can translate into later depression and anxiety symptoms. Furthermore, repeated measurements of psychosomatic complaints can be used to identify the most vulnerable group.